The rise of sea ice research collaboration between China and Finland - Leppäranta, Matti; Huiding, Wu; Zhanhai, Zhang; Zhijun, Li; Cheng, Bin (Polar Research Institute of China - PRIC, 2021)
Collaboration between China and Finland in marine sciences was commenced in winter 1988. The main topic was then short-term sea ice forecasting in the seasonal sea ice zone (SSIZ), particularly in the Bohai Sea in China and the Baltic Sea in Finland. The sea ice in SSIZ is thin and highly dynamic so that ice conditions may change rapidly. While the length scales of the Baltic Sea and the Bohai Sea are similar, the main difference between them is that the former is brackish and non-tidal while the latter is oceanic for the salinity and possesses a large tidal amplitude. The Bohai Sea is located at latitudes 37°N–41°N, and the Baltic Sea is located at latitudes 55°N–66°N. However, the same sea ice model is applicable for both. The main application field of sea ice forecasting was winter shipping in Finland and oil drilling in China. The collaboration was successful and in late 1990s the research was expanded to polar seas, lakes, and to climate change applications.